In Litopenaeus vannamei, the cuticular chitin-binding proteins LvDD9A and LvDD9B retard AHPND pathogenesis but facilitate WSSV infection. (July 2021) - Chen, Yi-Lun; Kumar, Ramya; Liu, Chun-Hung; Wang, Han-Ching
Abstract: Acute hepatopancreatic necrosis disease (AHPND) is a serious bacterial disease caused by V. parahaemolyticus strains which contain a virulent plasmid that encodes a binary pore-forming Pir toxin. Typically, these AHPND-causing bacteria first colonize in the shrimp stomach and then later cross to the hepatopancreas. To do this, they must pass through structural barriers which include the pliant cuticular lining of the stomach lumen. A previous transcriptomic study of shrimp challenged with the virulent 5HP strain of V. parahaemolyticus found significant upregulation of a contig associated with the cuticular proteins Lv DD9A and Lv DD9B. Here, we confirmed that the mRNA levels of these two genes were significantly upregulated not only in 5HP-infected shrimp, but also in the stomach of shrimp challenged with the white spot syndrome virus (WSSV). Using dsRNA-mediated gene silencing, we found that AHPND-causing bacteria migrated to the hepatopancreas within 3 h of AHPND infection in LvDD9A/B -silenced shrimp. Shrimp shell hardness of LvDD9A/B -silenced shrimp was also significantly decreased. Conversely, we found that silencing of LvDD9A/B significantly inhibited both WSSV gene expression and genome replication. Taken together, our data suggests that Lv DD9A and Lv DD9B are involved in both AHPND and WSSV infection. However, in AHPND, these cuticular proteins help to prevent bacterial migration from the stomach to the hepatopancreas, whereas in WSSV infection, they facilitate viral gene expression and genome replication. Highlights: The cuticular proteins LvDD9A/B were identified from white shrimp ( Litopenaeus vannamei ). The cuticular proteins LvDD9A/B were upregulated after challenge with both WSSV and AHPND. LvDD9A/B gene silencing decreases not only WSSV gene expression but also WSSV genome replication. Long-term LvDD9A/B gene silencing might lead to the reduction of the shrimp's exoskeleton hardness. Long-term LvDD9A/B gene silencing facilitates the migration of AHPND-causing bacteria to the hepatopancreas.